CHANGE MANAGEMENT, EMPLOYEES’ RESISTANCE, ORGANIZATIONAL COMMUNICATION, AND ORGANIZATIONAL COMMITMENT TOWARD CHANGE IMPLEMENTATION AT PT. BANK SULUTGO - Kasiaheng, Nova Alfiane; Lapian, Stanss L. H. V. J.; Tumbuan, Willem J. F. A. (Universitas Sam Ratulangi, 2021)
Change is inevitable. Every individual will go through changes every now and then. Organizations also undergo changes that happen to them. One of the industry in Indonesia that surely affected by changes and the developments that happening is the banking industry. With all the changes and developments that are happening simultaneously, it forces each organization to find solutions specifically for them, can be applied to the whole organization, and is in line with the organization’s goals and beliefs/value. This research aims to analyze Change Management, Employees’ Resistance, Organizational Communication, and Organizational Commitment toward Change Implementation at PT. Bank SULUTGO. This research uses Quantitative method and the data was collected through questionnaires. Multiple Linear Regression was used as the tool of analysis. The sample in this research are 58 employees of PT. Bank SULUTGO. The results of this research revealed that there is no any significant effect of Change Management toward the Change Implementation, there is no any significant effect of Employees’ Resistance toward Change Implementation, there is any significant effect of Organizational Communication toward Change Implementation, and there is any significant effect of Organizational Commitment toward Change Implementation. It is recommended for the organization to improve the systematic approach, tools, and resources to deal with changes.. Keywords: change management, employees’ resistance, organizational communication, organizational commitment, change implementation